2021
DOI: 10.1038/s41598-021-85628-1
|View full text |Cite|
|
Sign up to set email alerts
|

Anopheles ecology, genetics and malaria transmission in northern Cambodia

Abstract: In the Greater Mekong Subregion, malaria cases have significantly decreased but little is known about the vectors or mechanisms responsible for residual malaria transmission. We analysed a total of 3920 Anopheles mosquitoes collected during the rainy and dry seasons from four ecological settings in Cambodia (villages, forested areas near villages, rubber tree plantations and forest sites). Using odor-baited traps, 81% of the total samples across all sites were collected in cow baited traps, although 67% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
(67 reference statements)
2
39
0
Order By: Relevance
“…Many Anopheles samples were collected during the first hour of collection (between 6 pm and 7 pm), indicating that peak host-seeking behavior may occur earlier than 6 pm, possibly during the day time, especially in dark environments, such as in forest areas in Khanh Hoa and Binh Phuoc. This may not be an isolated observation as biting activity during the day was observed in Anopheles species in northern Cambodia ( Vantaux et al 2021 ), and in Laos ( Marcombe et al 2020 ). Herein, only CBT was conducted, thus, we were not able to infer the anthrophophily of Anopheles species in the malaria transmission context.…”
Section: Discussionmentioning
confidence: 83%
“…Many Anopheles samples were collected during the first hour of collection (between 6 pm and 7 pm), indicating that peak host-seeking behavior may occur earlier than 6 pm, possibly during the day time, especially in dark environments, such as in forest areas in Khanh Hoa and Binh Phuoc. This may not be an isolated observation as biting activity during the day was observed in Anopheles species in northern Cambodia ( Vantaux et al 2021 ), and in Laos ( Marcombe et al 2020 ). Herein, only CBT was conducted, thus, we were not able to infer the anthrophophily of Anopheles species in the malaria transmission context.…”
Section: Discussionmentioning
confidence: 83%
“…This study revealed a wide diversity of night-time human host seeking mosquito species in Sumba that potentially transmit multiple vector borne diseases. The presence of night biting vectors of non-malaria diseases warrants the careful application of the HLC technique to ensure the safety of volunteers conducting the mosquito trappings [ 53 , 54 ], or the implementation of other innovative tools for adult mosquito collection, such as the double net trap [ 55 ] and Host Decoy Trap [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria remains a serious public health challenge in Tropical Countries of the World especially in Sub-Saharan Africa [1,2]. The malaria disease is being transmitted by a Plasmodium-infected female Anopheles mosquito, when it comes in contact with the uninfected human host [3,4]. However, the uninfected Anopheles mosquito can also be infected with Plasmodium sppwhen it comes in contact with a Plasmodium-infected human host and it can retransmit the malaria disease.to another uninfected human host [5].…”
Section: Introductionmentioning
confidence: 99%